2016
DOI: 10.21767/2049-5471.100073
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Indigenous Womens Perspectives of Maternal Health and Health Care Services: A Systematic Review

Abstract: Development of policies and interventions to address health disparities between Indigenous and non-Indigenous populations requires a comprehensive understanding of Indigenous people's experiences and perspectives of healthcare services. We systematically reviewed the published literature on Canadian Indigenous women's experiences and perspectives of maternal healthcare during pregnancy, childbirth, and the postpartum period. Major bibliographic databases (including PubMed, CINAHL, EMBASE, SCOPUS, and SSCI) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 46 publications
(188 reference statements)
1
29
0
Order By: Relevance
“…This finding supports the results of Rono et al, that reports that Marakwet women may shun hospitals adrift of social and cultural values (18). Sharma et al, adds that, the current maternity approaches of women giving birth without the support of families disconnects and segregates mothers (19).…”
Section: Support and Companionship During Pregnancy Delivery And Possupporting
confidence: 88%
See 2 more Smart Citations
“…This finding supports the results of Rono et al, that reports that Marakwet women may shun hospitals adrift of social and cultural values (18). Sharma et al, adds that, the current maternity approaches of women giving birth without the support of families disconnects and segregates mothers (19).…”
Section: Support and Companionship During Pregnancy Delivery And Possupporting
confidence: 88%
“…The study infers that support services bestow native Marakwet woman power to exercise while passing along a modicum of labour and childbirth. This narrative is well documented (19,20,21). Furthermore, cultured birthing centre is known to provide greater involvement, satisfaction and attachment (19) as well as enhanced uptake of services (20).…”
Section: Support and Companionship During Pregnancy Delivery And Posmentioning
confidence: 99%
See 1 more Smart Citation
“…Returning again to the international literature, a systematic review addressing Canadian Indigenous women’s perspectives of maternal health care services [ 57 ] considered the policy environment which interrupts women’s access to appropriate health care, including access to smoking cessation programs. The review found that inconsistent advice provided to pregnant women who smoked, as well as factors such as substance abuse, unstable domestic situations and low socio-economic circumstances compromised the ability of women to attend cessation programs.…”
Section: Intersection Of Gender Trauma and Culturementioning
confidence: 99%
“…Sharma et al 2016's work is premised on the understanding the disparities of maternal health in Canada for Indigenous people and non-indigenous populations. Sharma et al (2016) find that "inconsistent and non-comprehensive policies" cause impediments to maternal health and healthcare access (341). Interestingly, Hole et al 2015's analysis of Indigenous peoples and culturally safe and unsafe care, contextualize the culturally unsafe care in the bureaucratic biomedical systems and which are physically placed in buildings that were the houses of colonist institutions (1668).…”
Section: Medical Practices Culturally Safe Carementioning
confidence: 99%